The Influence Of Location Promotion And Service Quality On Purchase Decisions (Survey Of Consumers At Anna Putra Store, Pasar Cikurubuk Tasikmalaya) - Alpi Nurunisa; Rita Tri Yusnita; Ai Kusmiati Asyiah (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to determine the effect of promotion, location and quality of service on purchasing decisions at the Anna Putra Store, Pasar Cikurubuk Tasikmalaya. The research method used is a quantitative method with a survey approach to 100 respondents who are consumers of Toko Anna Putra. The types of data used are primary data and secondary data. The data analysis technique used is multiple regression analysis. The results of this test prove that promotion, location and service quality have a significant effect simultaneously or partially on consumer purchasing decisions at Anna Putra Store, Pasar Cikurubuk Tasikmalaya